Gurus, Hired Guns, and Warm Bodies: Itinerant Experts in a Knowledge Economy - Mosco, Vincent (Labour / Le Travail, 2005)
The article reviews the book, "Gurus, Hired Guns, and Warm Bodies: Itinerant Experts in a Knowledge Economy," by Stephen R. Barley and Gideon Kunda.